Project Scheduling of the Garment Business Using CPM-Crashing based on the POM-QM Application for Windows - Ma. Elena C. Estebal; Dassy Jane Benogsudan (Research Synergy Press, 2024)
Taytay Rizal is known as the “Garment Capital of the Philippines” and is very popular among bargain-hunting shoppers. The garment industry is one of the major contributors to the municipalities’ economic growth. The emergence of fast fashion trends made the garment business in the municipality very lucrative. The industry, however, is highly competitive necessitating efficient management of planning of costs, schedules, and resources. The Critical Path Method (CPM) is an operations research technique that is useful for managers in managing projects and creating accurate project schedules. It is very useful in making optimal decisions in scheduling and determining critical activities to ensure the project’s earliest finish. This research aims to determine the project duration, costs, and critical path for a garment business startup using the POM-QM application for Windows. Descriptive research method was used where data was collected through literature reviews, direct observation, and interviews of garment shop owners and garment sub-contractors. Based on the results of the study, it can be concluded that the use of critical path method is necessary to complete the garment business project on time. The entire project will require 96 days of completion in normal time and a 15.67 percent increase in the garment business project costs was observed to shorten the project duration to 52 days. This study is limited to the garment shop owners and garment sub-contractors in Taytay Rizal and is further limited to garment business projects for ladies’ blouses and dresses.